The role of difficulties in emotion regulation on non-suicidal self-injury and suicide attempts: a cross-sectional study of Chinese adolescents - Hao Xu; Dianying Liu; Xuejing Xu; Jinghan Wang; Bixin Wang; Wenkai Zheng; Yan Chen; Wei Qu; Yunlong Tan; Zhiren Wang; Yanli Zhao; Shuping Tan (Scientific Reports)
Abstract Non-suicidal self-injury (NSSI) and suicide attempts (SA) among adolescents are issues of widespread concern. Non-suicidal self-injury and attempted suicide are both risk factors for suicide, and difficulties in emotion regulation (DER) may play a crucial role in their occurrence. Therefore, our study aims to investigate the role of DER in NSSI and SA among adolescents, which is of substantial clinical importance for the prevention and intervention of adolescent suicidal behaviors. A web-based questionnaire survey was administered to 9140 Chinese adolescents aged 12–18 years. Utilizing chain mediation and a threshold effect model, we investigated the impact of DER in relation to NSSI and SA among adolescents. DER had a direct and indirect effect on NSSI severity by amplifying depressive symptoms, which consequently increased the severity of NSSI. Furthermore, DER directly elevated the risk of SA by exacerbating depressive symptoms and NSSI severity. We observed a threshold effect, whereby the DER significantly increased the severity of NSSI after reaching a threshold score of 87. Our study provides valuable insights into the psychological mechanism of DER in relation to NSSI and SA among Chinese adolescents, underscoring the importance of intervention and prevention strategies aimed at addressing these underlying difficulties. These findings contribute to research on adolescent suicide and fill a knowledge gap in this field.